2019
DOI: 10.1093/tbm/ibz113
|View full text |Cite
|
Sign up to set email alerts
|

Low-income workers’ perceptions of wages, food acquisition, and well-being

Abstract: Although studies have demonstrated an association between increased economic resources and improvements in food security and health, there is a paucity of qualitative research regarding the relationships between household resources, food security, and health. Policy changes related to increasing low wages are potential opportunities to understand changes to material resources. The aims of this analysis were to describe how low-wage workers perceive household resources in relation to food acquisition and to exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Additionally, as highlighted by Beck and colleagues, time constraints, that are mainly experienced by women working in low-wage jobs due to lack of flexibility in work schedules, are a significant risk factor for food poverty (i.e. limited access to enough and nutritious food for an active healthy life) [ 85 , 86 ]. Therefore, it is imperative that future research aiming to improve food decisions among disadvantaged families consider lack of time as a barrier and seek ways to accommodate this in interventions, including flexibility with timing of interventions to account for parents’ schedules.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, as highlighted by Beck and colleagues, time constraints, that are mainly experienced by women working in low-wage jobs due to lack of flexibility in work schedules, are a significant risk factor for food poverty (i.e. limited access to enough and nutritious food for an active healthy life) [ 85 , 86 ]. Therefore, it is imperative that future research aiming to improve food decisions among disadvantaged families consider lack of time as a barrier and seek ways to accommodate this in interventions, including flexibility with timing of interventions to account for parents’ schedules.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, higher-income participants might be having access to food items with better nutritional qualities than lower-income participants, which in turn might lead to different patterns of the food group qualities even among participants with similar adherence scores and similar dietary patterns, due to their different income and access to good quality food. Beck et al33 observed that low-income participants dealt with a conflicting scenario: even though they would like to purchase higher quality foods, they often faced limiting trade-offs that prevented them from adjusting their food spending patterns. Likewise, the greater adherence to the MIND diet and greater consumption rates of many of its components among high-income participants was likely due, at least in part, to the costs of the diet components.…”
Section: Discussionmentioning
confidence: 99%
“…Much of the research on food acquisition has focused on the resourceful strategies low-income households use Fig. 1 Modified model of Campbell's framework for US household food security (3,4) to purchase foods (e.g. couponing and bulk purchases) and the contributions of federal food assistance to each household's food supply (5)(6)(7)(8)(9)(10)(11) .…”
Section: Household Food Productionmentioning
confidence: 99%
“…couponing and bulk purchases) and the contributions of federal food assistance to each household's food supply (5)(6)(7)(8)(9)(10)(11) . In determining whether alternative food acquisition ameliorates food insecurity, previous studies have utilised convenience samples from individuals already using at least one type of federal or community food assistance (4,12,(15)(16)(17)24,(27)(28)(29)(30)(31)(32)(33)(34) . To build on these results, we used data from the FoodAPS to characterise the use of alternative food sources in a nationally representative sample of low-income US households.…”
Section: Household Food Productionmentioning
confidence: 99%
See 1 more Smart Citation